NiFe-based bifunctional water decomposition electrocatalyst, preparation method and application
By designing a NiFe-based dual-function electrocatalyst, using a coral spherical three-dimensional self-supported core-shell heterostructure, the problems of high cost, low activity and poor stability of electrolytic catalysts in a dual-function catalytic environment are solved, and the alkaline The efficient catalysis in electrolytic water has promoted the efficiency of electrolytic water systems and the economic development of hydrogen energy.
Patent Information
- Application Number
- CN202411182040.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing electrolytic catalysts have problems such as high cost, low catalytic activity and poor stability in dual-function catalytic environments, which are difficult to match the catalytic environment of neutral and alkaline electrolytes, which affects the operating efficiency of the electrolytic system.
A NiFe-based bifunctional water decomposition electrocatalyst was designed, using a coral spherical three-dimensional self-supporting core-shell heterostructure, and the alkaline type coated NiFe-LDH is grown in situ on a foam nickel substrate by hydrothermal and solvothermal method. Cobalt carbonate nanowires form a unique graded porous structure, improving catalytic activity and stability.
It exhibits excellent OER and HER catalytic activity and high stability in alkaline electrolytic water, which reduces the cost of the electrolytic water system, improves the overall efficiency, and promotes the development of the hydrogen energy economy.
Smart Images

Figure CN119162604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis catalysts, and in particular to a NiFe-based bifunctional water decomposition electrocatalyst, a preparation method and an application thereof. Background Art
[0002] In the context of global clean energy transformation, hydrogen energy, as an efficient clean energy carrier, is gaining increasing attention. Especially in the process of electrolyzing water to produce hydrogen using electricity generated by renewable energy sources such as solar energy and wind energy, hydrogen, as a zero-emission energy source, is of great significance for building a sustainable energy system. However, water electrolysis technology currently still faces two key challenges: high overpotential caused by low electrode reaction activity and insufficient stability of electrode materials. Traditionally, noble metal catalysts such as RuO2 and Pt are often used to catalyze the anodic oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER) in water electrolysis due to their excellent catalytic performance. However, the high cost and limited natural resources limit their large-scale commercial application. To this end, the development of efficient, stable and low-cost non-noble metal-based electrocatalysts has become a current research hotspot, aiming to reduce the electrode overpotential and enhance the catalytic performance. However, there are significant differences in the optimal catalytic environments of OER and HER. Neutral and alkaline electrolytes are conducive to OER, while acidic electrolytes are conducive to HER. This mismatch in catalytic environment may affect the operating efficiency of the entire water electrolysis system, and existing catalysts are difficult to match the two catalytic environments to achieve dual-functional electrocatalysis.
[0003] Existing electrolytic water catalysts still have problems such as high cost, low catalytic activity, and poor stability. Since the process of designing and synthesizing bifunctional, high-performance electrocatalysts widely involves many factors such as product components, ratios, microstructures, and preparation processes, it is necessary to make comprehensive choices among multiple factors and construct a unique and efficient microstructure in order to overcome the constraints of mismatched catalytic environments through the coordination of multiple aspects; due to the many technical difficulties that still exist, existing technologies cannot solve these problems and synthesize bifunctional, high-performance electrocatalysts.
[0004] Therefore, adopting new technical concepts, overcoming problems such as catalytic environment mismatch from multiple aspects, and designing and synthesizing OER / HER bifunctional electrocatalysts with high cost-effectiveness, high activity and stability are of great significance for improving the overall efficiency of water electrolysis systems, reducing costs, and promoting the development of the hydrogen energy economy. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of the bifunctional water electrolysis catalyst in the prior art, such as the inability to overcome the mismatch of the catalytic environment, high cost, low catalytic activity, low stability, etc., and adopt a new technical concept to provide a NiFe-based bifunctional water decomposition electrocatalyst, a preparation method and its application. By combining components, ratios and processes, an OER / HER electrocatalyst with a unique microstructure, high cost performance, high activity and stability is designed and synthesized, so that the bifunctional electrocatalyst is a coral spherical three-dimensional self-supporting nickel foam-loaded NiFe-LDH@Co-CH / NF core-shell heterostructure, which exhibits excellent OER / HER catalytic activity and high stability in an alkaline water electrolysis system, and is applied to catalyze the OER and HER processes of water electrolysis, thereby improving the overall efficiency of the water electrolysis system and reducing the cost.
[0006] In order to achieve the above object, the technical solution provided by the present invention is:
[0007] A NiFe-based bifunctional water splitting electrocatalyst, characterized in that it is a core-shell heterostructured, three-dimensional self-supporting NiFe-based OER / HER bifunctional electrocatalyst, specifically a coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF with a three-dimensional hierarchical porous core-shell heterostructure.
[0008] The NiFe-based bifunctional water splitting electrocatalyst has a coral spherical layered heterogeneous structure, with nickel foam as a conductive substrate, Co-CH nanowires as an inner layer, the diameter of the inner layer is 230-250nm, and it is evenly distributed on the nickel foam substrate; NiFe-LDH nanosheets are used as an outer layer, and the width of the outer layer is 170-190nm; the coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF is in-situ grown on the nickel foam conductive substrate.
[0009] A method for preparing a NiFe-based bifunctional water splitting electrocatalyst, wherein the bifunctional electrocatalyst NiFe-LDH@Co-CH / NF is prepared by a two-step hydrothermal and solvothermal method using nickel foam as a conductive substrate, wherein a basic cobalt carbonate nanowire precursor is in situ grown by a hydrothermal method, and a layer of NiFe-LDH nanosheets is further compounded on the outer layer of the basic cobalt carbonate nanowire by a solvothermal method, so that the catalyst has a self-supporting, layered, core-shell heterogeneous structure and a unique hierarchical porous structure, wherein the hierarchical porous structure increases the surface area and the number of active sites, optimizes the electron transport path, promotes mass transfer and product release, and improves the OER / HER bifunctional electrocatalytic performance; the method comprises the following steps:
[0010] S1: Substrate pretreatment: Foam nickel (NF, 2×3 cm2 Block) is pre-treated to ensure a clean surface as a conductive NF substrate;
[0011] S2: Preparation of NF-loaded basic cobalt carbonate nanowire precursor: Soak the pretreated conductive NF substrate in a pink transparent aqueous solution containing an appropriate amount of ammonium fluoride, cobalt salt, and urea for 10 minutes, transfer them into a reactor, heat to 120°C and react for 5 hours; after the reaction, take out the conductive NF substrate, wash it with ultrapure water to remove surface impurities and dry it to obtain the basic cobalt carbonate nanowire precursor Co-CH / NF;
[0012] S3: Preparation of catalyst: The cleaned Co-CH / NF was placed in a yellow-brown ethanol dispersion containing an appropriate amount of urea, iron salt, and nickel salt, and transferred to a reactor together, heated to 90°C and reacted for 10 hours. After the reaction was completed and cooled to room temperature, the product was washed with ultrapure water and dried to obtain NiFe-LDH@Co-CH / NF.
[0013] The cobalt salt in steps S2 and S3 is Co(NO3)2·6H2O, the nickel salt is Ni(NO3)2·6H2O, and the iron salt is Fe(NO3)3·6H2O.
[0014] The invention discloses an application of a NiFe-based bifunctional water splitting electrocatalyst in oxygen evolution and hydrogen evolution reaction of water electrolysis as a bifunctional catalyst for OER and HER; specifically, a coral spherical NiFe-based core-shell heterostructure bifunctional electrocatalyst is used as the anode and cathode active materials of a full water splitting battery. The core-shell heterostructure electrocatalyst NiFe-LDH@Co-CH / NF reaches 100mAcm in alkaline oxygen evolution reaction. -2 The overpotential required for the high current density is only 240mV. In the alkaline hydrogen evolution reaction, only 91mV overpotential is required to reach 10mAcm -2 When the core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF was used as anode and cathode in the same alkaline electrolytic cell for water electrolysis performance testing, the current density was 10 mA cm -2 The battery voltage is 1.60V at a current density of , and can run stably for more than 90 hours.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects:
[0016] 1. The NiFe-based bifunctional water splitting electrocatalyst, preparation method and application thereof provided by the present invention adopt a new technical concept, and through the simultaneous improvement and mutual combination of components, proportions and processes, an OER / HER electrocatalyst NiFe-LDH@Co-CH / NF with a unique hierarchical porous microstructure, high cost performance, high activity and stability is designed and synthesized as a whole, and the bifunctional electrocatalyst has a coral spherical three-dimensional self-supporting nickel foam loaded core-shell heterogeneous structure, which solves the problem that the bifunctional catalyst cannot overcome the mismatch of the catalytic environment, and exhibits excellent OER / HER catalytic activity and high stability in the alkaline water electrolysis system; when the catalyst is applied to the OER and HER process of catalytic water electrolysis, the structure of the water electrolysis system can be simplified as a whole, the overall efficiency of the water electrolysis system can be improved, and the cost can be reduced, and it can promote the development of efficient and economical water electrolysis technology and promote the construction of green hydrogen energy economy, etc., showing broad potential and application prospects.
[0017] 2. The present invention successfully synthesized a three-dimensional self-supporting coral spherical core-shell heterostructure bifunctional electrocatalyst. During the synthesis process, by controlling the process conditions of the hydrothermal and solvothermal two-step preparation methods, coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterials (NiFe-LDH@Co-CH / NF) were in situ grown on a foam nickel substrate, so that the electrocatalyst NiFe-LDH@Co-CH / NF has a unique coral spherical shape and hierarchical porous and layered heterogeneous structure; wherein, its hierarchical porous structure increases the surface area and the number of active sites, promotes mass transfer and product release, so that the catalyst exhibits excellent electrocatalytic performance, and simultaneously improves the catalytic activity, stability and cost-effectiveness of the catalyst, solving the problems of high cost, low catalytic activity, low stability and the like of the bifunctional catalyst for water electrolysis in the prior art.
[0018] 3. The preparation method provided by the present invention is a self-supporting electrocatalyst, which uses nickel foam as a conductive substrate, in-situ grows a basic cobalt carbonate nanowire precursor by a hydrothermal method, and further compounds a layer of NiFe-LDH nanosheets on the outer layer of the basic cobalt carbonate nanowire by a solvothermal method. This layered heterogeneous structure allows the catalyst to expose more active sites, accelerates the diffusion and transfer of the electrolyte solution, and thus improves the catalytic activity of the catalyst.
[0019] 4. The bifunctional catalyst provided by the present invention has an inner layer of basic cobalt carbonate nanowires grown on porous nickel foam, and an outer layer of NiFe-LDH nanosheets. The heterogeneous heterostructure interface between the inner and outer layers not only increases the surface area but also optimizes the electron transfer path, reduces the interfacial potential barriers of mass transfer kinetics and charge transfer, thereby improving the electrocatalytic performance of OER and HER.
[0020] 5. The core-shell heterostructure bifunctional electrocatalyst synthesized in the present invention has excellent alkaline OER / HER catalytic activity, which is of great significance for the further development and assembly of efficient and stable bifunctional electrocatalytic water electrolysis systems.
[0021] 6. The core-shell heterostructure electrocatalyst and preparation method thereof provided by the present invention use transition metals as raw materials, which reduces the production cost. The synthesis method is simple and easy to operate, has few operation steps, high preparation efficiency and is environmentally friendly, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0023] Figure 1 is a scanning electron microscope image (SEM) of NiFe-LDH@Co-CH / NF prepared in Example 1.
[0024] Figure 2 (a) is a transmission electron microscopy (TEM) image of NiFe-LDH@Co-CH / NF prepared in Example 1;
[0025] Figure 2 (b) is a high-resolution transmission electron microscopy (HRTEM) image of the NiFe-LDH@Co-CH / NF prepared in Example 1.
[0026] Figure 3 This is the energy dispersive spectrometer (EDS) of the NiFe-LDH@Co-CH / NF prepared in Example 1.
[0027] Figure 4 (a) is the OER polarization curve of NiFe-LDH@Co-CH / NF prepared in Example 1, Co-CH / NF prepared in Comparative Example 1, NiFe-LDH / NF prepared in Comparative Example 2, and nickel foam in an alkaline environment of 1.0 M KOH.
[0028] Figure 4 (b) is the HER polarization curves of NiFe-LDH@Co-CH / NF prepared in Example 1, Co-CH / NF prepared in Comparative Example 1, NiFe-LDH / NF prepared in Comparative Example 2, and nickel foam in an alkaline environment of 1.0 M KOH.
[0029] Figure 5 The polarization curve diagram (a) and stability test diagram (b) of the water electrolysis device (NiFe-LDH@Co-CH / NF(-,+)) in which the NiFe-LDH@Co-CH / NF prepared in Example 1 is assembled as both the anode and the cathode. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments so that those skilled in the art can implement the invention with reference to the description.
[0031] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0033] Basic Example
[0034] A NiFe-based bifunctional water splitting electrocatalyst is a core-shell heterostructured, three-dimensional self-supporting NiFe-based OER / HER bifunctional electrocatalyst, specifically a coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF with a three-dimensional hierarchical porous core-shell heterostructure.
[0035] The NiFe-based bifunctional water splitting electrocatalyst has a coral spherical layered heterogeneous structure, with nickel foam as a conductive substrate, Co-CH nanowires as an inner layer, the diameter of the inner layer is 230-250nm, and it is evenly distributed on the nickel foam substrate; NiFe-LDH nanosheets are used as an outer layer, and the width of the outer layer is 170-190nm; the coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF is in-situ grown on the nickel foam conductive substrate.
[0036] A method for preparing a NiFe-based bifunctional water splitting electrocatalyst, wherein the bifunctional electrocatalyst NiFe-LDH@Co-CH / NF is prepared by a two-step hydrothermal and solvothermal method using nickel foam as a conductive substrate, wherein a basic cobalt carbonate nanowire precursor is in situ grown by a hydrothermal method, and a layer of NiFe-LDH nanosheets is further compounded on the outer layer of the basic cobalt carbonate nanowire by a solvothermal method, so that the catalyst has a self-supporting, layered, core-shell heterogeneous structure and a unique hierarchical porous structure, wherein the hierarchical porous structure increases the surface area and the number of active sites, optimizes the electron transport path, promotes mass transfer and product release, and improves the OER / HER bifunctional electrocatalytic performance; the method comprises the following steps:
[0037] S1: Substrate pretreatment: Foam nickel (NF, 2×3 cm 2 Block) is pre-treated to ensure a clean surface as a conductive NF substrate;
[0038] S2: Preparation of NF-loaded basic cobalt carbonate nanowire precursor: Soak the pretreated conductive NF substrate in a pink transparent aqueous solution containing an appropriate amount of ammonium fluoride, cobalt salt, and urea for 10 minutes, transfer them into a reactor, heat to 120°C and react for 5 hours; after the reaction, take out the conductive NF substrate, wash it with ultrapure water to remove surface impurities and dry it to obtain the basic cobalt carbonate nanowire precursor Co-CH / NF;
[0039] S3: Preparation of catalyst: The cleaned Co-CH / NF was placed in a yellow-brown ethanol dispersion containing an appropriate amount of urea, iron salt, and nickel salt, and transferred to a reactor together, heated to 90°C and reacted for 10 hours. After the reaction was completed and cooled to room temperature, the product was washed with ultrapure water and dried to obtain NiFe-LDH@Co-CH / NF.
[0040] The cobalt salt in steps S2 and S3 is Co(NO3)2·6H2O, the nickel salt is Ni(NO3)2·6H2O, and the iron salt is Fe(NO3)3·6H2O.
[0041] The invention discloses an application of a NiFe-based bifunctional water splitting electrocatalyst in oxygen evolution and hydrogen evolution reaction of water electrolysis as a bifunctional catalyst for OER and HER; specifically, a coral spherical NiFe-based core-shell heterostructure bifunctional electrocatalyst is used as the anode and cathode active materials of a full water splitting battery. The core-shell heterostructure electrocatalyst NiFe-LDH@Co-CH / NF reaches 100mAcm in alkaline oxygen evolution reaction. -2 The overpotential required for high current density is only 240 mV. In the alkaline hydrogen evolution reaction, only 91 mV overpotential is required to reach 10 mA cm -2 When the core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF was used as anode and cathode in the same alkaline electrolytic cell for water electrolysis performance testing, the current density was 10 mA cm -2 The battery voltage is 1.60V at a current density of , and can run stably for more than 90 hours.
[0042] In terms of bifunctional electrocatalyst design, this embodiment makes full use of the unique chemical properties and structural advantages of NiFe layered double hydroxide (NiFe-LDH), and combines the preparation process, components, and ratios to construct the microstructure. The special layered structure of NiFe-LDH can accelerate the release and transfer of gas products in the solution by increasing the diffusion and transfer rate of water molecules, and the synergistic effect between different components can improve the electrocatalytic performance. The NiFe-LDH prepared in this embodiment not only has the advantages of flexible chemical composition, degradation resistance, excellent OER catalytic activity and durability in alkaline media. The present invention overcomes the problem of slow HER kinetics and reduced HER performance due to the high energy barrier of the Volmer step. In addition, the present invention also overcomes the problem of high electrode overpotential required to drive HER and OER processes due to relatively slow electrokinetic characteristics. In summary, the present invention designs and synthesizes a bifunctional electrocatalyst based on NiFe-LDH with efficient microstructure and high performance by making comprehensive choices in catalyst components, ratios, processes and other factors, which is of great significance for the industrialization of water electrolysis.
[0043] Example 1
[0044] This embodiment is a specific implementation based on the basic embodiment.
[0045] See attached Figure 1-5 The present embodiment provides a NiFe-based bifunctional water splitting electrocatalyst and a preparation method thereof. The catalyst is NiFe-LDH@Co-CH / NF obtained by in situ growing NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterials on a nickel foam substrate by a hydrothermal method and a solvothermal method. The catalyst has a coral ball-shaped appearance and a layered heterogeneous microstructure as a whole, and has a porous structure inside the coral ball-like skeleton. The porous structure is also similar to the shape of carnation petals. It is a nanoscale layered, porous bifunctional electrocatalyst with a core-shell heterogeneous structure.
[0046] During the preparation process, the catalyst adopts a self-supporting design and uses nickel foam as a conductive substrate. The basic cobalt carbonate nanowire precursor is first grown in situ on the nickel foam by a hydrothermal method, and then a layer of NiFe-LDH nanosheets is further compounded on the outer layer of the basic cobalt carbonate nanowire by a solvothermal method. This layered heterogeneous structure can effectively expose more active sites while increasing the surface area, and accelerate the diffusion and transfer of the electrolyte solution, thereby significantly improving the catalytic activity of the catalyst.
[0047] The preparation method of the NiFe-based bifunctional water splitting electrocatalyst (core-shell heterostructure bifunctional electrocatalyst) specifically comprises the following steps:
[0048] Step S1: Treat nickel foam (NF) with 1.0M hydrochloric acid solution and ethanol to ensure the surface is clean as a conductive substrate layer; specifically, place the nickel foam in 1.0M HCl solution, ultrasonicate for 15 minutes, then rinse with deionized water 2-3 times, place the rinsed nickel foam in ethanol, ultrasonicate for 15 minutes, and obtain the treated nickel foam as a conductive NF substrate.
[0049] Step S2: dispersing appropriate amounts of ammonium fluoride, cobalt nitrate and urea into appropriate amounts of ultrapure water to obtain a transparent and uniformly dispersed pink aqueous solution; specifically: dissolving 0.873 g Co(NO3)2·6H2O, 0.3704 g NH4F and 1.5015 g Co(NH2)2 in 35 ml ultrapure water, and ultrasonicating until the solution is uniformly dispersed to obtain a transparent pink aqueous solution; in the pink aqueous solution, the amount of ammonium fluoride is 0.3704 g, the amount of cobalt nitrate is 0.873 g, and the amount of urea is 1.5015 g;
[0050] The obtained pink aqueous solution and a clean piece of NF (pre-cut 2cm×3cm 2 The pink aqueous solution was heated to 120°C and kept for 5 hours. After the reaction was completed, the solution was cooled to room temperature. The obtained Co-CH / NF sample was washed with ultrapure water and ethanol and then dried to obtain the basic cobalt carbonate nanowire precursor Co-CH / NF.
[0051] Step S3: dispersing an appropriate amount of urea, ferric nitrate, and nickel nitrate into an appropriate amount of ethanol to obtain a uniformly dispersed, transparent yellow-brown solution, specifically, dissolving 0.0967 g Ni(NO3)2·6H2O, 0.1345 g Fe(NO3)3·9H2O, and 0.06 g Co(NH2)2 in 35 ml ethanol, and ultrasonicating until the solution is uniformly dispersed to obtain a transparent yellow-brown solution;
[0052] The transparent yellow-brown solution was transferred to a 50 ml hydrothermal reactor, and the Co-CH / NF precursor obtained above was added. The reactor was placed in an oven and heated to 90 ° C for 10 h. After the reaction was completed, it was cooled to room temperature. The product was washed with deionized water and ethanol, and then dried. After drying, the target product NiFe-LDH@Co-CH / NF sample was obtained.
[0053] The electrocatalyst prepared by the above method has a core-shell heterogeneous structure, which is a basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF coated with NiFe-LDH with an overall coral spherical shape, wherein the Co-CH nanowire is used as an inner layer with a diameter of 230-250nm and is evenly distributed on the nickel foam conductive substrate layer; the NiFe-LDH nanosheet is used as an outer layer with a width of 170-190nm.
[0054] The catalyst prepared by the above method is a heterogeneous structure NiFe-LDH@Co-CH / NF catalyst, which has a three-dimensional self-supporting hierarchical porous structure and a heterogeneous interface. It can increase the surface area and the number of active sites while improving the electron transfer rate and mass transfer resistance, thereby significantly improving the catalytic effect and stability of OER and HER.
[0055] The core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF exhibits excellent OER performance at 100 mA cm -2 The overpotential is 240 mV at a current density of 10 mA cm -2 The overpotential is 91 mV at a current density of .
[0056] The core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF has excellent water electrolysis performance. When the catalyst is used as anode and cathode in an alkaline electrolytic cell for water electrolysis performance testing, the electrolysis performance is 10 mA cm -2 The battery voltage is 1.60V at a current density of .
[0057] The synthesis method of the core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF provided in this embodiment has a simple process, is easy to operate, has low equipment requirements, and has low production cost. It also provides corresponding technical guidance for the preparation of other self-supporting bifunctional electrocatalysts.
[0058] Comparative Example 1
[0059] Dissolve 0.873 g Co(NO3)2·6H2O, 0.3704 g NH4F, and 1.5015 g Co(NH2)2 in 35 ml ultrapure water, and sonicate until the solution is uniformly dispersed to obtain a transparent pink solution.
[0060] The transparent pink solution was transferred to a 50 ml hydrothermal reactor, and a piece of treated nickel foam (2 cm × 3 cm) was added. The reactor was placed in an oven and heated to 120 °C for 5 h. After the reaction was completed, it was cooled to room temperature. The product was washed with deionized water and ethanol, and dried to obtain Co-CH / NF.
[0061] Comparative Example 2
[0062] Dissolve 0.0967g Ni(NO3)2·6H2O, 0.1345g Fe(NO3)3·9H2O, and 0.06g Co(NH2)2 in 35ml ethanol, and sonicate until the solution is uniformly dispersed to obtain a transparent yellow-brown solution.
[0063] The transparent yellow-brown solution was transferred to a 50 ml hydrothermal reactor, and a piece of treated nickel foam (2 cm × 3 cm) was added. The reactor was placed in an oven and heated to 90 °C for 10 h. After the reaction was completed, it was cooled to room temperature. The product was cleaned with deionized water and ethanol, and dried to obtain NiFe-LDH / NF.
[0064] The core-shell heterogeneous bifunctional electrocatalyst NiFe-LDH@Co-CH / NF prepared in the above embodiment of the present invention is obtained by constructing the microstructure through a two-step hydrothermal and solvothermal method. Figure 1 and attached Figure 2 The SEM and TEM images of the NiFe-LDH@Co-CH / NF catalyst show that the catalyst was successfully prepared. The overall shape of the catalyst is a coral sphere, with an inner layer of basic cobalt carbonate nanowires and an outer layer of NiFe-LDH nanosheets.
[0065] The EDS of NiFe-LDH@Co-CH / NF is shown in the attached Figure 3 As shown, it can be seen that Co, Ni, Fe, and O coexist, and the ratio of Co / (Ni+Fe) is 1:1.1. The catalyst is composed of an inner layer of basic cobalt carbonate nanowires and an outer layer of NiFe-LDH nanosheets. The catalyst has a unique multilayer heterogeneous structure, which is conducive to increasing the specific surface area of the catalyst, while effectively exposing more active sites and accelerating the diffusion and transfer of the electrolyte solution, thereby significantly improving the catalytic activity of the catalyst.
[0066] As attached Figure 4 As shown in a, compared with the Co-CH / NF (η 100 =330mV,η 500 =390mV) and NiFe-LDH / NF in Comparative Example 2 (η 100 =270mV,η 500 =330 mV), the NiFe-LDH@Co-CH / NF catalyst exhibited excellent OER performance (η 100 =240mV,η 500 =290mV).
[0067] As attached Figure 4 As shown in b, compared with the Co-CH / NF (η 10=124mV) and NiFe-LDH / NF in Comparative Example 2 (η 10 =149 mV), the NiFe-LDH@Co-CH / NF catalyst exhibited excellent HER performance (η 10 =91 mV). It is worth noting that the electrolytic water system assembled with the catalyst as anode and cathode also exhibited excellent electrolytic water performance.
[0068] As attached Figure 5 As shown in a, the NiFe-LDH@Co-CH / NF(-,+) water electrolysis device is at 10 mA cm -2 At a current density of 1.50 V, the battery voltage is only 1.60 V, indicating that it has excellent water electrolysis performance. After 90 h of stability test, the battery voltage still remains 99.4% (see Appendix Figure 5 b), indicating that it has excellent stability.
[0069] The bifunctional electrocatalyst NiFe-LDH@Co-CH / NF prepared by the hydrothermal and solvothermal two-step method in the above embodiment of the present invention has a core-shell heterogeneous structure and a unique hierarchical porous structure. The hierarchical porous structure increases the surface area and the number of active sites, optimizes the electron transport path, and promotes mass transfer and product release, so that the catalyst exhibits excellent electrocatalytic performance.
[0070] The embodiment of the present invention provides a synthetic method for preparing a bifunctional electrocatalyst, which uses fewer components, has a simple and convenient process and is easy to operate, has a low production cost, and also has certain reference significance for preparing other self-supporting bifunctional electrocatalysts.
[0071] The NiFe-based bifunctional water splitting electrocatalyst, preparation method and application thereof provided by the above embodiment of the present invention is a core-shell heterogeneous structure, a three-dimensional self-supporting NiFe-based OER / HER bifunctional electrocatalyst, specifically a coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF with a three-dimensional hierarchical porous core-shell heterogeneous structure; it uses nickel foam as a conductive substrate, the inner layer is a basic cobalt carbonate nanowire, and the outer layer is a NiFe-LDH nanosheet, and the microstructure is constructed by hydrothermal and solvothermal steps; because the catalyst has a unique hierarchical heterogeneous structure, it greatly enriches the active sites on the catalyst surface, significantly accelerates the diffusion and transfer of the electrolyte solution, and the strong electronic interaction between the outer layer of the NiFe-LDH nanosheet and the Co-CH nanowire interface stimulates the synergistic effect and electron transfer, thereby improving the catalytic activity of the catalyst. The catalyst has excellent OER and HER performance, and the electrolytic water system assembled by the catalyst also has excellent electrolytic water performance. The core-shell heterostructure bifunctional electrocatalyst provided by the present invention has broad potential and application prospects in promoting the development of efficient and economical water electrolysis technology and promoting the construction of a green hydrogen energy economy.
[0072] It should be particularly pointed out that within the scope of the components, ratios and process parameters recorded in the present invention, other technical solutions obtained by specific selection can achieve the technical effects of the present invention, so they are no longer listed one by one. At the same time, other catalyst technical solutions obtained by using the components, ratios, preparation methods and applications equivalent to those recorded in the present invention are all included in the protection scope of the present invention.
[0073] In the description of the present invention, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In the present invention, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A NiFe-based bifunctional water splitting electrocatalyst, characterized in that: It is a core-shell heterostructured, three-dimensional self-supporting NiFe-based OER / HER bifunctional electrocatalyst, specifically a coral-shaped NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF with a three-dimensional hierarchical porous core-shell heterostructure.
2. The NiFe-based bifunctional water splitting electrocatalyst according to claim 1, characterized in that The invention has a coral spherical layered heterogeneous structure, with nickel foam as a conductive substrate, Co-CH nanowires as an inner layer, the inner layer having a diameter of 230-250nm and being evenly distributed on the nickel foam substrate; NiFe-LDH nanosheets as an outer layer, the outer layer having a width of 170-190nm; the coral spherical NiFe-LDH-coated basic cobalt carbonate nanowire nanomaterial NiFe-LDH@Co-CH / NF is in-situ grown on the nickel foam conductive substrate.
3. A method for preparing a NiFe-based bifunctional water splitting electrocatalyst, characterized in that: The bifunctional electrocatalyst NiFe-LDH@Co-CH / NF was prepared by a two-step hydrothermal and solvothermal method using nickel foam as a conductive substrate. The basic cobalt carbonate nanowire precursor was first grown in situ by a hydrothermal method, and then a layer of NiFe-LDH nanoflakes was compounded on the outer layer of the basic cobalt carbonate nanowire by a solvothermal method, so that the catalyst has a self-supporting, layered, core-shell heterogeneous structure and a unique hierarchical porous structure. The hierarchical porous structure increases the surface area and the number of active sites, optimizes the electron transfer path, promotes mass transfer and product release, and improves the OER / HER bifunctional electrocatalytic performance.
4. The preparation method according to claim 3, characterized in that: It includes the following steps: S1: Substrate pretreatment: The nickel foam was pretreated with hydrochloric acid solution and ethanol to ensure a clean surface as a conductive NF substrate; S2: Preparation of NF-loaded basic cobalt carbonate nanowire precursor: soak the pretreated conductive NF substrate in a pink transparent aqueous solution containing an appropriate amount of ammonium fluoride, cobalt salt, and urea for 10 minutes, transfer them into a reactor, heat and react; after the reaction, take out the conductive NF substrate, wash it with ultrapure water, remove surface impurities and dry it to obtain the basic cobalt carbonate nanowire precursor Co-CH / NF; S3: Preparation of catalyst: The cleaned Co-CH / NF was placed in a yellow-brown ethanol dispersion containing an appropriate amount of urea, iron salt, and nickel salt, and transferred to a reactor together, heated to an appropriate temperature, and reacted for an appropriate time. After the reaction was completed and cooled to room temperature, the product was washed with ultrapure water and dried to obtain NiFe-LDH@Co-CH / NF.
5. The preparation method according to claim 4, characterized in that: The cobalt salt in step S2 is Co(NO3)2·6H2O; in 35 ml of pink transparent aqueous solution, the amount of ammonium fluoride is 0.3704 g, the amount of cobalt salt is 0.873 g, and the amount of urea is 1.5015 g; the heating method is hydrothermal, heated to 120°C for reaction for 5 hours.
6. The preparation method according to claim 4, characterized in that: The cobalt salt in step S3 is Co(NO3)2·6H2O, the nickel salt is Ni(NO3)2·6H2O, and the iron salt is Fe(NO3)3·6H2O; in the yellowish brown ethanol dispersion, the amount of urea is 0.06g, the amount of iron salt is 0.1345g, the amount of nickel salt is 0.0967g, and the ethanol is 35ml.
7. The preparation method according to claim 4, characterized in that: The appropriate temperature in step S3 is 90° C., and the appropriate time is 10 hours.
8. Use of the NiFe-based bifunctional water splitting electrocatalyst according to claim 1 or 2 in oxygen evolution and hydrogen evolution reactions by water electrolysis as a bifunctional catalyst for OER and HER.
9. The use according to claim 8, characterized in that: The core-shell heterostructured electrocatalyst NiFe-LDH@Co-CH / NF achieved 100 mA cm in alkaline oxygen evolution reaction. -2 The overpotential required for the high current density is only 240mV. In the alkaline hydrogen evolution reaction, only 91mV overpotential is required to reach 10mAcm -2 of current density.
10. The use according to claim 8, characterized in that: When the core-shell heterogeneous structure electrocatalyst NiFe-LDH@Co-CH / NF was used as anode and cathode in the same alkaline electrolytic cell for water electrolysis performance testing, the electrocatalyst NiFe-LDH@Co-CH / NF showed a good electrolysis performance at 10 mA cm -2 The battery voltage is 1.60V at a current density of , and can run stably for more than 90 hours.
Citation Information
Patent Citations
Hydrothermal and electrodeposition combined preparation method for iron oxyhydroxide-nickel iron hydrotalcite oxygen evolution electrode
CN109837558A
Hydrothermal-assisted preparation method for iron oxyhydroxide-nickel iron hydrotalcite integrated electrode
CN109837559A
Nickel-iron-molybdenum hydrotalcite nanowire bifunctional electrocatalyst and preparation method thereof
CN111871421A
Self-supporting oxygen evolution electrode and preparation method and application thereof
CN115478296A
Nickel-cobalt-based hydrotalcite-basic cobalt carbonate composite electrode material and preparation method and application thereof
CN118390100A
